The Role of Labor Costs in Regional Capital Formation - Garofalo, Gasper A.; Fogarty, Michael S. (The Review of Economics and Statistics, 1987)
High labor costs in large Midwestern metropolitan areas have significantly reduced their manufacturing capital stock. For the period 1974 to 1978, the authors estimate that sixteen metropolitan areas in the Midwest, taken together, had approximately $2.8 billion less capital stock than they would have had if their labor costs had been at the national average. This difference is equal to 4 percent of the capital stock in these areas. The results are simulated from the estimation of a labor demand equation that is derived from a generalized Leontief cost function. Copyright 1987 by MIT Press.